Variability of Sound Speed Profile in the Banda Sea During West and East Monsoon - Sari, Ratna Juita; Yuliardi, Amir Yarkhasy; Nugroho, Agung Tri; Rahmalia, Diah Ayu; Manik, Agustina Sartika Yos Ekaristi (Jurnal Sains dan Teknologi Perikanan, 2025)
Sound speed in the ocean is a key parameter for underwater acoustic applications, such as communication, navigation, and sonar systems. Sound speed is influenced by temperature, salinity, and pressure, making it highly sensitive to seasonal oceanographic dynamics. Although the Banda Sea is recognized as one of the strongest upwelling centers in Indonesia, studies specifically addressing the seasonal variability of sound speed profiles in this region remain limited. This study aims to analyze the differences in temperature, salinity, and sound speed characteristics between the west and east monsoon periods in the Banda Sea. Monthly temperature and salinity data for 2023 from the Copernicus Marine Environment Monitoring Service (CMEMS) with a spatial resolution of 0.083° × 0.083° were processed using Ocean Data View (ODV). Sound speed was analyzed in terms of its horizontal and vertical distributions at depths of 0, 150, and 300 m, as well as vertical profiles down to 500 m. During the west monsoon (January), surface temperature was higher (29.5–31 °C) and sound speed reached maximum values (1543–1546 m/s), with a deeper thermocline due to downwelling. In contrast, during the east monsoon (July), surface temperature was lower (26.5–28.5 °C), the halocline was shallower (34.7–35.2 PSU at 50–150 m), and surface sound speed decreased (1538–1541 m/s), reflecting seasonal upwelling. Minimum sound speed was consistently observed at 300–500 m (1496–1505 m/s). These findings highlight temperature as the dominant factor controlling sound speed, with important implications for the planning of underwater acoustic operations in eastern Indonesian waters.